A descriptive and comparative study of the instructional objectives of teachers of chemistry, English, French, geography, history and mathematics at grade twelve level in English-speaking high schools of the Ottawa Board of Education - Connelly, Desmond J (University of Ottawa (Canada), 1972)
Abstract not available.
Keywords: Education, Language and Literature.; Education, Mathematics.; Education, Instructional Design.; Education, Secondary.; Education, Social Sciences.; Education, Sciences.